Análise paramétrica de escoamento particulado aplicado ao preenchimento de fraturas - Barbosa, Marcos Vinicius (2015)
Among the most diverse types of multiphase flow, the particulate flow raises interest due to its presence in several systems such as farmaceutical, chemical and oil and gas indus- try. Specifically in the oil and gas industry the particulate flow may be applied upon the appearence of the invasion phenomenon, characterized by the fluid loss to the reservoir, associated to the presence of fractures. Particles with selected granulometry are added to the mud in order to fill the fratures and reestablish circulation. In this line, the aim of this work is to investigate the particulate flow applied to the filling of a perfectly retangular and impermeable fracture. The flow is mathematicaly modeled by an eulerian approach applied to the continuous phase (fluid) and by a lagrangian approach applied to the discrete phase (particles). The numerical models used to attain the solution of the problem are the Dense Discrete Phase Model (DDPM) which accounts for the coupling between the phases and the Discrete Element Method (DEM) which calculates particle collision. The analysis shows the influence of the fracture length (hF R ), flow paramenters (Reynolds number - Re and dynamic viscosity - μβ ), particle parameters (diameter - Dp and specific mass ratio between particles and fluid - ρp/β ) and parameters of the injection process (number of injected particles - Np,inj ) on the formation of the bed. Such influence is analyzed through the length (hpct ) and heigth (hpct ) of the bed and the vertical filling of the fracture (epct ). An optimal bed would be capable to attain a fluid loss close to zero in the least time possible (test ) by forming itself very close to the fracture entering, having a minimum length and a maximum height. In order to obtain the optimized bed, the pressure on the channel inlet (pm,CH,i ) should be monitored to guarantee that the fracturing pressure is not surpassed by the buildup pressure generated by the particles injection. This pressure is analyzed by the initial pressure on the inlet channel, before the particle injection, and the pressure drop generated by the fracture. Results indicate that all sensitivity parameters can alter the geometric characteristics of the bed, showing a direct influence on reducing the fluid loss through the fracture and on the filling time.